(untitled) (Singaporean Journal of Business Economics and Management, 2016)
The aim of this study is to investigate the state of leadership in a leading company and the effectiveness of the leadership on organisational and employee performance. It will serve to investigate how effective leadership and communication can be used as a strategy to offer new direction to an organisation and to explore the best approach to leadership in changing organisational circumstances. The focus of this study is to establish if there is a connection between the lack of effective leadership communication and the average performance of employees. This company also represents a suitable case study for investigating the phenomenon of leadership and its impact on organisational and employee performance.